Critical social psychology an introduction - Gough, Brendan; McFadden, Majella; McDonald, Matthew (Houndmills, Basingstoke Palgrave Macmillan, 2013)
What can critical social psychology teach us about our sense of identity? How have psychosocial and feminist approaches challenged our understanding of subjectivity? Where is this complex and fast-moving field heading? This new edition addresses these questions and more, providing important insight into social psychology. Thoroughly updated and revised, it clearly outlines approaches such as social constructionism and psychoanalysis, and explains how these ideas can illuminate topics like social influence and prejudice. This text includes two new chapters on applied health psychology and applied work psychology ; uses 'critical thinking boxes' to demonstrate the practical application of theory and debates, helping you engage with the different ideas ; contains revised content including an expanded section on research methods, as well as enhanced coverage of action research and critical narrative approaches.
Critical Social Psychology Applied : Critical Health Psychology -- Critical Work Psychology -- Reflections on Critical Social Psychology.
Includes bibliographical references (pages 300-342) and index.
Keywords: Social psychology